INTEGRAL REPRESENTATIONS AND THE SYSTEM OF DIFFERENTIAL EQUATION OF HYPERGEOMETRIC TYPE IN PARTIAL DERIVATIVES OF THE FOURTH ORDER FOR A FUNCTION (Scientific journal of the Fergana State University, 2022)
This article studies the properties of the Kampe de Feriet function  of two fourth-order arguments. Integral representations and a system of differential equations in partial derivatives of hypergeometric type, which is satisfied by the indicated function, are proved.